2003
DOI: 10.1002/ijc.11269
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tumor‐associated antigens by screening phage‐displayed human cDNA libraries with sera from tumor patients

Abstract: Screening cDNA libraries from solid human tumors with sera of autologous patients (SEREX) has proven to be a powerful approach to identifying tumor antigens recognized by the humoral arm of the immune system. In many cases, application of this methodology has led to the discovery of novel tumor antigens as unknown gene products. We tried to improve the potency of the SEREX approach by combining it with phage-display technology. We designed a new lambda vector to express protein fragments as N-terminal fusions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 44 publications
0
77
0
Order By: Relevance
“…There is considerable evidence that the immune system produces an autoantibody response to neoplastic cells (16)(17)(18). The detection of such autoantibodies has been shown to have diagnostic and prognostic value (16,17,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence that the immune system produces an autoantibody response to neoplastic cells (16)(17)(18). The detection of such autoantibodies has been shown to have diagnostic and prognostic value (16,17,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The cDNA fragments encoding the antigenic regions of the Toxoplasma gondii antigens MIC2, MIC3, SAG1, GRA3, GRA7, and M2AP (3,5) were assembled by PCR to give the chimeric antigens EC2 and EC3 (Fig. 1), which were then cloned into vector pGEX-SN (25). This resulted in the production of GST-fusion proteins and allowed their purification from E. coli cells under native conditions by one-step affinity chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting DNA was purified and mixed with the PCR product of M2AP, and the mixture was used as the template for DNA amplification with primers K563 and K568 (30 cycles of 30 s at 94°C, 30 s at 45°C, and 180 s at 72°C) to generate the chimeric antigen EC3. Finally, the DNA products of EC2 and EC3 were digested with the SpeI and NotI restriction endonucleases and subcloned into the bacterial vector pGEX-SN (25). Table 1 shows the oligonucleotides used for the construction of the recombinant EC2 and EC3 antigens.…”
Section: Methodsmentioning
confidence: 99%
“…Studies reported that an immune response in the form of autoantibodies against certain tumor antigens develops in many cancer patients (12)(13)(14)(15), therefore subsequent studies attempted to use these autoantibody signatures to measure the immune response in prostate cancer and utilize it as a possible early detection method for the disease (15). Prostate cancer can avoid the immune defenses by presenting a defective antigen, expressing immunosuppressive molecules, T cell receptor dysfunction, and active immune down-modulation (16).…”
Section: Identification Of Immunity-related Genes In Prostate Cancer mentioning
confidence: 99%